Interactive Governance: Management of Potential Migrants in the Development of Nagari Sumanik, West Sumatra Province - Miftahul Viona Sari; Syamsurizaldi Syamsurizaldi; Hendri Koeswara (Universitas Teuku Umar, 2022)
This study aims to see how the interaction process by Nagari Sumanik Government in managing migrants potentialities for the village development from the interactive governance perspective according to Torfing, et al. This research is using the qualitative type of research with a descriptive approach. The results are indicating that in managing the migrants potentialities for the village development, they have been using the interactive governance perspective, which can be seen in the institutional design variable that the village government has designed the institutional according to their potential which is by incorporating the elements of Rantau into the vision and mission of the village of Sumanik and forming the field of Rantau outside from the structure of the nagari government and also involves migrants as the network actors for the village development. In the Goal and Framework Steering variable, the relation between the village government and the migrants is coordination and more informal. In the process management variable, the Nagari Sumanik Government is taking the input and suggestions from migrants so that it can encourage innovation in development. In the direct participation variable, Nagari government has built the migrants trust by maintaining communication to provide the migrants understanding about the village conditions and the migrant support implementing programs that the benefits can be directly felt by the people of Nagari Sumanik. The interaction process is still dominated by the Wali Nagari and several special figures, and the Nagari social institutions involvements seems not enough. The function of this institution is important to optimize the migrant participations for the village development.